Seasonal variation of gastro-intestinal helminths of three bat species in the dry forest of western Mexico - Valeria B. Salinas-Ramos; L. Gerardo Herrera; David I. Hernández-Mena; David Osorio-Sarabia; Virginia León-Règagnon (Revista Mexicana de Biodiversidad)
Studies on helminths of chiropterans are relatively uncommon compared to those of other animals, and seasonal changes in helminth load have been rarely examined. We characterized the gastro-intestinal helminth load of 3 bats species to test for the existence of seasonal changes in response to known seasonal environmental and bat prey fluctuations. We did not find seasonal variation in most of the cases. However, the prevalence of 4 endoparasite species was significantly higher during one of the seasons. The highest richness was registered in Pteronotus parnellii during the wet season. The effective number of species was higher during the dry season in the 3 species of Pteronotus. Diet seems to be an important driver of helminth infracommunity structure, but we found heterogeneous patterns in the relationship between diversity and load of helminths and seasonal patterns of bat’s diets and abundance of potential intermediate hosts.